PENGARUH KUALITAS PELAYANAN, WORD OF MOUTH, DAN BRAND IMAGE TERHADAP KEPUTUSAN PENGGUNAAN JNE CABANG SEMARANG - Rika Estika Putri; Handoyo Djoko Waluyo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
High levels of population mobility caused the need for courier services is important in supporting the mobility of global society , either for personal or business interests. JNE is one of the biggest courier company in Indonesia which has a mission to give the best experience for customer consistently. The achievement total of JNE branch Semarang has fluctuating not only from the target but also from the delivery total income since 2012 through 2014. This type of research is using explanatory research. The sample of this research are 100 respondents, and data collection techniques through questionnaires and interview using accidental sampling. Quantitative data were analyzed through the validity, reliability, crosstab, correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F test using SPSS for Windows version 15. The results show that service quality, word of mouth and brand image have partial and simultaneous effect to using decision. Brand image provides the most effect on using decision of JNE Branch Semarang. The suggestions that can be given in this research are the company expected to increase the service quality especially for the JNE’s employee, and also can re-arrange the capacity of service providers facility, and increase the quality of delivery so there’s no delay anymore.